Muscle Strength, Oxygen Saturation and Physical Activity in Patients with Chronic Exertional Compartment Syndrome Compared to Asymptomatic Controls - Lisa Urup Tønning; Bjarne Mygind-Klavsen; Troels Kjeldsen; Ulrik Dalgas; John Brincks; Inger Mechlenburg (North American Sports Medicine Institute, 2023)
# Background One of the most common causes of exercise-induced pain in the lower leg is chronic exertional compartment syndrome (CECS). Research is limited on muscle strength, oxygen saturation and physical activity in patients with CECS. # Purpose To compare muscle strength, oxygen saturation, and daily physical activity between patients with CECS and matched asymptomatic controls. A secondary purpose was to investigate the association between oxygen saturation and lower leg pain in patients with CECS. # Study Design Case-control study. # Method Maximal isometric muscle strength of the ankle plantar and dorsiflexors was tested in patients with CECS and sex- and age-matched controls using an isokinetic dynamometer and oxygen saturation (StO~2~) during running was tested by near infrared spectroscopy. Perceived pain and exertion were measured during the test using the Numeric Rating Scale and Borg Rating of Perceived Exertion scale and the exercise-induced leg pain questionnaire. Physical activity was assessed by accelerometry. # Results Twenty-four patients with CECS and 24 controls were included. There were no differences in maximal isometric plantar or dorsiflexion muscle strength between patients and controls. Baseline StO~2~ was 4.5pp (95% CI: 0.7;8.3) lower for patients with CECS than for controls, whereas no difference existed when they experienced pain or reached exhaustion. No differences were found in daily physical activities, except that on average, patients with CECS spent less time cycling daily. During the StO~2~ measurement, patients experienced pain or reached exhaustion while running significantly earlier than the controls (p<0.001). StO~2~ was not associated with leg pain. # Conclusion Patients with CECS have similar leg muscle strength, oxygen saturation and physical activity levels as asymptomatic controls. However, patients with CECS experienced significantly higher levels of lower leg pain than the controls during running, daily activities and at rest. Oxygen saturation and lower leg pain were not associated. # Level of Evidence Level 3b.